Dietary Calcium Intake and Associated Factors among Pregnant Women in Southern Benin in 2014 - Agueh, VICTOIRE DAMIENNE; Tugoué, Madeleine Flore; Sossa, Charles; Métonnou, Clémence; Azandjemè, Colette; Paraiso, Noel Moussiliou; Ouendo, Marius-Edgard; Ouédraogo, Laurent T.; MAKOUTODE, MICHEL (My University, 2015)
Hypertensive and its complications during pregnancy are closely linked to maternal mortality and morbidity. Sufficient calcium intake during pregnancy reduces the risk of hypertensive disorders. The objective is to determine dietary calcium intake and associated factors in pregnant women in southern Benin. This cross-sectional study included 176 pregnant women selected by random cluster sampling. Calcium intake was determined from two non-consecutive 24 hours dietary recalls. Demographic and socioeconomic factors were collected from individual interviews. Multivariate logistic regression model was used to identify factors associated with calcium intake controlling for energy intake. The mean daily calcium intake was 561.69 ± 183.02 mg and the median intake was 560.74 mg per day. The percentage of pregnant women with low calcium intake was 94.60%. The women in the lower economic status tercile (OR = 0.520 95% CI 0.415 - 0.653) were less likely to have calcium intakes above the median compared to the upper tercile of economic status. Women with secondary or more education level (OR = 1.961 95% CI 1.505 - 2.555) showed a higher odd ratio to have dietary calcium intake above the median value compared to those with no schooling. Low calcium intake was widespread among pregnant women. Calcium supplements and interventions to promote optimal nutrition in pregnant women are needed to protect them from low calcium intake consequences.
Keywords: Calcium; Dietary Intake; Pregnancy; Benin